(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In comparison to adults, children have a higher risk of perioperative respiratory and cardiovascular problems due to their distinct respiratory and circulatory physiology. Due to their inability to control breathing and innate sensitivity to quick desaturation, airway obstruction, early respiratory fatigue, and lung atelectasis, anaesthesia can exacerbate respiratory decline in young children. Premature newborns (less than 60 weeks postconceptional age) are at risk for persistent apnoea and the resulting deterioration of respiratory function. In neonates, the transitional phase of circulation is susceptible to reverting to persistent foetal circulation. In comparison to older children and adults, the myocardium and autonomic regulation of the heart are young and distinct in neonates and babies, making them susceptible to life-threatening haemodynamic alterations during the perioperative period. In this review, we examine the variations in respiratory and cardiovascular physiology between neonates, babies, and younger children and older children and adults. We concentrate primarily on the transitional physiology of the respiratory and circulatory systems in neonates and infants, as well as the detrimental changes that can occur during anaesthesia or perioperative care.